Innovations in Packaging Waste Management through Corporate Social Responsibility - Soulthoni, Hannin PN; Itasari, Maya (Universitas Pakuan, 2025)
This study explores corporate social responsibility (CSR) initiatives and innovations in packaging waste management implemented by PT. Indofood Sukses Makmur Tbk, one of Indonesia’s largest food and beverage companies. Amid rising concerns over plastic waste and its impact on marine ecosystems, the research examines how Indofood’s CSR programs—namely the Waste Bank Program, Green Warmindo Initiative, and Drop Box Program—contribute to sustainability and the circular economy. Employing a qualitative approach, the study uses document analysis of official CSR and sustainability reports from 2021 to 2023, complemented by cross-referenced data from industry publications and government policies. The findings reveal that Indofood successfully recycled over 1,000 tons of plastic waste within three years, increased public awareness of recycling practices, and strengthened community participation in waste management. Furthermore, its collaboration with PRAISE and IPRO underscores the company’s effort to establish an integrated waste management ecosystem aligned with Sustainable Development Goals (SDG) 12 and 14. Despite significant progress, challenges remain in expanding program coverage, particularly in rural areas and regions with limited recycling infrastructure. The study concludes that corporate CSR can serve as a catalyst for environmental innovation, combining economic, social, and ecological objectives to promote sustainable industry transformation in Indonesia’s food and beverage sector.